1992
DOI: 10.1017/s0272263100010457
|View full text |Cite
|
Sign up to set email alerts
|

L2 Working Memory Capacity and L2 Reading Skill

Abstract: Working memory capacity refers to the ability to store and process information simultaneously in real time and has been shown to correlate highly with first language (L1) reading skill. This study examines the sensitivity of second language (L2) working memory capacity to differences in reading skill among advanced L2 learners. The index of working memory capacity used was the reading span test (Daneman & Carpenter, 1980). Subjects with larger working memory capacities scored higher on measures of reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
312
5
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(343 citation statements)
references
References 13 publications
22
312
5
4
Order By: Relevance
“…It assessed two working memory components, processing and storage (e.g., Chun & Payne, 2004;Daneman & Carpenter, 1980;Harrington & Sawyer, 1992;Lesser, 2007;Waters & Caplan, 1996). The participants had to view each math problem, calculate the simple addition or subtraction problem and say their answer aloud while their answer was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…It assessed two working memory components, processing and storage (e.g., Chun & Payne, 2004;Daneman & Carpenter, 1980;Harrington & Sawyer, 1992;Lesser, 2007;Waters & Caplan, 1996). The participants had to view each math problem, calculate the simple addition or subtraction problem and say their answer aloud while their answer was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The researcher then suggested that future studies should assess individuals' WMC in several moments during the course of L2 acquisition/learning so as to verify to what extent WM scores vary as a function of L2 proficiency. As advanced by several researchers (HARRINGTON, 1992;HARRINGTON and SAWYER, 1992;BERQUIST, 1998), L2 proficiency might be the key factor determining the low correlations between L1 and L2 working memory scores, suggesting that, whereas the former may refer to a biological endowment, the latter may be related to the amount of knowledge of the language one possesses. To scrutinize the relationship between WMC in L1 and in L2 and to examine the effects of L2 proficiency on WM scores variation are the main goals of the current study.…”
Section: Individual Differences In Working Memory Capacity and Speechmentioning
confidence: 97%
“…As claimed before, one possible explanation for this finding is the fact that as L2 proficiency level increases, knowledge of the language becomes more automatized requiring thus less attentional resources from working memory to be executed. According to infor mation processing models, ROSSMAN;McLEOD, 1983;HULSTIJN;HULSTIJN, 1984;BIALYSTOK, 1994;), L2 learning involves the development of a cognitive skill that requires practice and attentional resources to develop HEREDIA, 1996).…”
Section: Does Working Memory Capacity Vary According To Proficiency?mentioning
confidence: 99%
“…In a study by Harrington and Sawyer (1992), 32 native Japanese speakers learning English as an L2 were asked to complete an English and Japanese version of the reading span test, along with two subsections of the Test of English as a Foreign Language (TOEFL). Results showed that readers with higher L2 reading span scores had a better performance on the subsections of the TOEFL tested; the improved performance was associated with correlation coefficients of .57 (grammar section) and .54 (reading and vocabulary section).…”
Section: Working Memory and Llearningmentioning
confidence: 99%